Difusi Inovasi Smart Kampung Manis sebagai Bentuk Komunikasi Digital Smart City - Nabila Shofaa; Bachruddin Ali Akmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the digital communication implemented through the Smart Kampung Manis program in strengthening Smart City and to analyze public acceptance of the digital services. The research used a qualitative approach with a descriptive exploratory type. Data collection techniques included observation, semi-structured interviews, and documentation. The analysis employed the Diffusion of Innovation Theory and Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2). The results show that Smart Kampung Manis has improved public services and facilitated community access to administrative services. However, its implementation has not been optimal due to limited network infrastructure, lack of inter-agency coordination, and limited human resources. The community showed positive responses toward the convenience and benefits of the digital services provided. Keywords: Diffusion Of Innovation, Digital Communication, Smart City, Smart Kampung Manis, UTAUT-2.